Honey bee (Apis mellifera) queen quality: host-microbial transcriptomes exploring the influence of age and hindgut symbiont Commensalibacter melissae - Duan C. Copeland; Oliver L. Kortenkamp; Brendon M. Mott; Charles J. Mason; Kirk E. Anderson (Animal Microbiome)
Abstract Understanding the biological mechanisms underlying extreme lifespan variation within species remains a fundamental challenge in aging research. Here, we investigated the role of gut microbiota and age in honey bee (Apis mellifera) queens combining 16S rRNA gene sequencing and transcriptomics. Analysis of 40 queen hindguts revealed that Commensalibacter melissae (Alpha 2.1) relative abundance was significantly higher in young queens compared to old queens. Using queens with the highest and lowest C. melissae relative abundance, RNA sequencing identified 1451 differentially expressed genes associated with C. melissae abundance, twice the number associated with age alone (719 genes). Queens with high C. melissae abundance showed distinct transcriptional profiles related to stress response, protein homeostasis, and longevity-regulating pathways, particularly genes involved in oxidative stress response and cellular maintenance. Our analysis revealed complex relationships between age, C. melissae abundance, and gene expression patterns, suggesting that multiple interacting factors contribute to queen quality. These findings contribute to our understanding of host-microbe interactions in honey bee queens and highlight the intricate relationship between gut microbiota composition and host physiology in honey bees.